Effect of pressure and temperature on Raman scattering and an anharmonicity study of tin dichalcogenide single crystals. (January 2015) - Bhatt, Sandip V.; Deshpande, M.P.; Sathe, Vasant; Chaki, S.H.
Abstract: Raman spectra of Tin dichalcogenide (SnS2 and SnSe2 ) single crystals have been measured at high pressures up to 20 GPa and low temperatures up to 80 K. The present study indicates a good stability of these compounds at high pressure and low temperature. Here, we report a detailed temperature-dependent Raman spectroscopic study of A 1g phonon mode of Tin dichalcogenide by considering the contributions from thermal expansion and lattice anharmonicity and analyze the data based on known anharmonicity model. Highlights: Raman spectroscopic studies of SnS2 and SnSe2 single crystal synthesized by chemical vapour transport technique as a function of pressure (0–12 GPa) and temperature (80–300 K). Isobaric and isothermal mode Gruneisen parameters have been determined from the temperature and pressure dependent Raman spectra for both Raman active modes. This study indicates a good structural stability of SnS2 and SnSe2 single crystal. Anharmonic parameters calculated for the Raman active modes.